2015
DOI: 10.1152/ajpendo.00458.2014
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide reverses adipose tissue inflammation and insulin resistance upon loss of ovarian function

Abstract: We hypothesized that carbon monoxide (CO) might suppress chronic inflammation, which led to metabolic disturbances. Ovariectomy (OVX) was performed in mice to mimic chronic inflammation secondary to loss of ovarian function. OVX increased fat mass and the infiltration of highly inflammatory CD11c cells into adipose tissue (AT), resulting in a disturbance of glucose metabolism. Treatment of CO attenuated these; CO decreased recruitment of CD11c-expressing cells in AT and reduced expression of CD11c in bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Recent findings have demonstrated that thermogenic capability sufficient to decrease body weight is induced by a specific stimulus in the process of WAT browning, in which the adipocytes are stimulated to upregulate typical genes of brown adipose tissue (BAT; Barbatelli et al, 2010). Since we and others have demonstrated that OVX increases fat mass, body weight, and metabolic rates without changes in food intake (Choi et al, 2014(Choi et al, , 2015Kim et al, 2013;Rogers et al, 2009), we hypothesized that OVX decreases browning in AT, leading to weight gain. OVX induced significant increases in body weight starting from 8 weeks after OVX, without any significant changes in food intake ( Figure 1a…”
Section: Ovx Decreases Browning In Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have demonstrated that thermogenic capability sufficient to decrease body weight is induced by a specific stimulus in the process of WAT browning, in which the adipocytes are stimulated to upregulate typical genes of brown adipose tissue (BAT; Barbatelli et al, 2010). Since we and others have demonstrated that OVX increases fat mass, body weight, and metabolic rates without changes in food intake (Choi et al, 2014(Choi et al, , 2015Kim et al, 2013;Rogers et al, 2009), we hypothesized that OVX decreases browning in AT, leading to weight gain. OVX induced significant increases in body weight starting from 8 weeks after OVX, without any significant changes in food intake ( Figure 1a…”
Section: Ovx Decreases Browning In Atmentioning
confidence: 99%
“…Postmenopausal women experience various metabolic syndrome components including insulin resistance (Stefanska, Bergmann, & Sypniewska, 2015) and osteoporosis (Lorentzon, 2019). In animal models, ovariectomy (OVX) results in insulin resistance and fatty liver, with increased visceral fat and chronic inflammation (Choi et al, 2015; Kim et al, 2013; Rogers, Perfield 2nd, Strissel, Obin, & Greenberg, 2009), and exhibits a pattern of pathogenesis similar to diet‐induced obesity (DIO). The development of pathogenesis in DIO has been reported to be caused by increased fat mass, leading to the accumulation of adipose tissue macrophages (ATMs) that actively participate in chronic inflammation (Lumeng, Bodzin, & Saltiel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adipose tissue produces classic cytokines (tumor necrosis factor-α, TNF-α, interleukin-6), chemokines (interleukin-8, monocyte chemoattractant protein-1, MCP-1), hormones (angiotensin II, adrenomedullin, atrial natriuretic peptide), growth factors, enzymes and enzyme inhibitors (visfatin, vaspin, plasminogen activator inhibitor-1) and acute phase proteins. Adipose tissue secretes also non-protein biologically active mediators including gasotransmitters (NO, CO and H 2 S) [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Adipose Tissue—an Overviewmentioning
confidence: 99%
“…Globally, it is expected to afflict around 500 million people by 2030 (Gustafson, Hedjazifar, Gogg, Hammarstedt, & Smith, ). Although several mechanisms, including inflammation (Choi et al, ), oxidative stress, and mitochondrial dysfunction (Wright et al, ), have been reported to be involved in insulin resistance, the molecular underpinnings of insulin resistance and insulin signaling impairments are only partially understood.…”
Section: Introductionmentioning
confidence: 99%